Implementation of task continuity management in banking service activities and treasury operations for smooth payment system - Nugraha, Taufan Anggara; Djakman, Chaerul D. (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The increasing complexity and unpredictability of future business environments, including threats such as terrorism, natural disasters, and pandemics like COVID-19, necessitates robust business continuity management (BCM) to ensure the uninterrupted functioning of critical operations. This study aims to evaluate the effectiveness of Bank XYZ's Business Continuity Management, particularly focusing on its Task Continuity Management (TCM) within banking services and treasury operations. Using a case study approach, data were collected through interviews, document analysis, and observations at Bank XYZ, and evaluated against the ISO 22301:2019 standard for “Security and Resilience - Business Continuity Management Systems – Requirements.” The findings indicate that Bank XYZ's BCM generally aligns with ISO 22301:2019, covering aspects such as organizational context, leadership, planning, and continuous improvement. However, the evaluation also identified areas for enhancement, including broader risk assessment, improved communication, better competency development programs, and more comprehensive testing and monitoring methods. The study concludes with recommendations for industry, education, and public sectors to improve BCM practices by focusing on risk assessment, communication, competency development, and effective evaluation methods.